ACTIVITY BASED COSTING DENGAN KENDALI WAKTU UNTUK MENGHITUNG COST LAYANAN PADA BENGKEL OTOMOTIF â€œDAâ€ DI JEMBER - Kustono, Alwan Sri; Nanggala, Ardhya Yudistira Adi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
One of the weaknesses of many small businesses that are encountered is the weak reporting of quantitative business activities. A common problem that occurs is about how the treatment of costs for the activities of the small and medium business units that are not in accordance with existing accounting principles. The recognition and measurenment of costs incurred in small and medium enterprises is very important to understand. It can support their entrepreneurs to make decisions, such as to determine the selling price that affects the profits to be achieved by a business. The purpose of this study uses activity based costing techniques with time drivers to calculate service costs in the